Effectiveness of Kinesio Taping and Exercises for Pronated Feet in Children with Neurodevelopmental Disorders: A Cross Over Study - Parmar, S; Dhanuka, H; Shetty, D (Nigerian journal of clinical practice, 2022)
Background: Taping is widely used intervention in various conditions treated by physiotherapist. Neurodevelopmental disorders in children leading to foot abnormality is one of the major concen. As taping is one of the intervention in same the study is focusing taping on pronated feet in the selected age group. Aim: The aim of this study was to investigate whether the kinesiotaping and exercise improve pronated feet in neurodevelopmental disordered (NDD) children. Patients and Methods: This was a cross over study, within subjects study evaluating two treatments, kinesio tape, and exercise. Thirty subjects with age group 6-12 years diagnosed with NDD having pronated feet. Subjects were allocated in the two groups. Group 1 included subjects for taping and Group 2 included subjects for exercise. Taping was applied for two consecutive weeks for 5 days per week and then 2 weeks of the window period, which was followed by two consecutive weeks of exercise sessions for 5 days per week. The navicular drop test and Foot Posture Index were measured pre and post treatment. Foot posture index used to examine the posture of foot and navicular drop test. Results and Conclusion: Group 1 (taping) and Group 2 (exercises) showed no significant results as a single entity, whereas there was a small effect seen of the intervention.